Hepatic Hilar Nerve Block for Adjunctive Analgesia in Thermal Ablation of Liver Tumors: A Prospective Randomized Controlled Trial - Georgiades, Marilena; March, Christine; Barajas Ordonez, Felix; Omari, Jazan; Powerski, Maciej; Grosser, Oliver S; Damm, Robert; Pech, Maciej (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2025)
To determine whether performing a temporary hepatic hilar nerve block in patients undergoing microwave or radiofrequency ablation of primary or secondary hepatic malignancies reduces the requirement for intravenous conscious procedural sedation and analgesia.Fifty patients undergoing percutaneous image-guided liver thermal ablation were included in this single-center prospective randomized controlled trial. The experimental arm received a hepatic hilar nerve block in addition to intravenous medication directly before thermal ablation, whereas the control group underwent thermal ablation solely under intravenous medication, with the possibility of crossover. Student’s t-test and analysis of covariance were performed to determine the block’s efficacy regarding the intraoperative medication requirement.50 patients (22 females, 28 males) were randomly allocated to two groups without significant differences between the cohorts’ baseline patient, clinical, and tumor characteristics. Three control group patients underwent crossover. Initial analysis using Student’s t-test revealed no significant intravenous medication reduction in the control group vs. the test group (190 µg vs. 189 µg fentanyl, P = 0.96 and 1.34 mg vs. 1.60 mg Midazolam, P = 0.19). Thus, ANCOVA was performed to accommodate for heterogeneous ablation conditions (ablation time, total energy applied, affected liver capsule area). The adjusted mean fentanyl dosage was 206 µg vs. 184 µg (control group vs. test group), yielding a significant reduction after block (P = 0.020). None of the patients who received a hepatic hilar nerve block experienced any adverse events during a mean follow-up of nearly six months (range: 0–17 months).This prospective randomized trial confirms that a hepatic hilar nerve block can be safely performed before liver tumor thermal ablation as an adjunct to intravenous medication to reduce opioid consumption and manage pain.
Keywords: Nerve block; Pain; Adult liver cancer; ablation procedures; interventional procedures